FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA TATA KELOLA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Mega Utami; Yohanes Yohanes (Universitas Katolik Indonesia Atma Jaya, 2023)
This study aims to examine the effect of the variables of independent commissioners, audit committees, corporate social responsibility, profitability, firm size, leverage, institutional ownership on tax avoidance. The object of research is manufacturing companies listed on the IDX from 2018 to 2020. The study uses a purposive sampling method in selecting the sample, consisting of 32 companies listed on the IDX from 2018 to 2020 and total of 96 research sample data. Multiple linear regression model was used as a method of data analysis. The results show that independent commissioners, audit committees, corporate social responsibility, firm size, leverage, and institutional ownership have no effect on tax avoidance, while profitability has an influence on tax avoidance. Companies do tax avoidance because the amount of tax borne is based on the amount of profit earned, making the company have the opportunity to do tax planning to reduce the amount of tax liability.